Constitutive equation of butter at static loading - Šárka Nedomová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
This study focuses on the constitutive modelling of finite deformation in the commercially obtained butter (composition is 83 % of milk fat) at the temperature 17–20 °C. The specimens from the butter (height L0=14.6 mm and diameter 20 mm) have been compressed between two parallel metal plates at a fixed crosshead speed 20 mm/min using of the testing device TIRA TEST. The force F and the deformation ∆L are measured during compression and both quantities are recorded. The experimental records force F – displacement (deformation) were obtained. These records have been transformed into stress–strain dependences and into true stress–true strain. The basic data on the strain behaviour of a butter under low strain rates have been obtained. Experimental results show that the behaviour of butter can be described by a hyperelastic material model. In this model, the quasi–static response is defined by compressible hyperelasticity, whereby the strain energy potential is assumed to be representable by a newly proposed polynomial series with three independent parameters. The material parameters in the constitutive model are determined from compression test. A comparison of predictions based on the proposed constitutive equation with experiments shows that the model is able to describe the strain behaviour of the butter examined.